Pengaruh Financial Distress dan Opinion Shopping terhadap Penerimaan Opini Audit Going Concern: Studi Empiris pada Perusahaan Sektor Pertambangan Terdaftar di Bursa Efek Indonesia tahun 2018-2022 - Irfan Irsyad; Nelvirita Nelvirita (Jurnal Eksplorasi Akuntansi, 2024)
This study aims to examine the effect of financial distress, and opinion shopping on going concern audit opinion acceptance. The population in this study were all mining sector companies listed on the Indonesia Stock Exchange in 2018-2022. The sampling technique used is purposive sampling. The number of samples used in this study were 75 samples. Hypothesis testing is done by analyzing using data panel regression methods. The results showed that financial distress has a positive effect on going concern audit opinion acceptance, and opinion shopping has no effect on going concern audit opinion acceptance in mining sector companies listed on the Indonesia Stock Exchange in 2018- 2022.